Interactive English Online Teaching System Based on B/S Model - Wanhong Gu; Yaxiong Yuan (Advances in Multimedia)
In order to improve the effect of online interactive teaching of English, this paper analyzes the online interactive teaching data of English in combination with the generation of confrontation network and simulates the human interaction process to perform simulation. Moreover, this paper introduces the strategy gradient of reinforcement learning to the generator of the generation confrontation network to solve the problem that the generation confrontation network is difficult to be used for dialogue generation. In addition, this paper combines intelligent algorithms to construct an online interactive teaching system for English. The experimental research results show that the interactive English online teaching system based on the B/S model proposed in this paper has a greater advantage than the traditional online English teaching method.